2020
DOI: 10.1177/1071181320641177
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Dynamic Resilience using First-process Autoregressive Modelling: An Empirical Study

Abstract: Dynamic resilience is a temporal process that reflects individuals’ capability to overcome task-induced stress and sustain their performance during task-related events. First-order autoregressive (AR(1)) modelling is posited for measuring individuals’ dynamic resilience over time. The current research investigated this by testing 30 adults in a dynamic decision-making task. AR(1) modelling was conducted on the data, and was compared against a modified seismic resilience metric for concurrent validity purposes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…To summarize, dynamic resilience presents a relatively new model of resilience that may hold valued sensitivity in human performance evaluation. However, while Crameri et al (2020b)'s dynamic resilience measure has revealed sensitivity in classifying individuals into dynamic resilience groups based on in-task performance, further research needs to be conducted to identify if dynamic resilience characteristics links to selfregulating cognitive structures that play a role in mediating physiological adaptations during task engagement. To address this, this paper aims to evaluate the application of the dynamic resilience measure on vmHRV.…”
Section: Physiological Manifestations Of Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…To summarize, dynamic resilience presents a relatively new model of resilience that may hold valued sensitivity in human performance evaluation. However, while Crameri et al (2020b)'s dynamic resilience measure has revealed sensitivity in classifying individuals into dynamic resilience groups based on in-task performance, further research needs to be conducted to identify if dynamic resilience characteristics links to selfregulating cognitive structures that play a role in mediating physiological adaptations during task engagement. To address this, this paper aims to evaluate the application of the dynamic resilience measure on vmHRV.…”
Section: Physiological Manifestations Of Stressmentioning
confidence: 99%
“…The task manipulations of the phase conditions were identical to those presented by Crameri et al (2020b). Together, these task manipulations were designed to acquire data suitable for dynamic resilience evaluation.…”
Section: Task Manipulationsmentioning
confidence: 99%
See 3 more Smart Citations